Promoting health : the primary health care approach 6E - Talbot, Lyn; Verrinder, Glenda (Chatswood, NSW : Elsevier Australia, 2018)
In Promoting Health the authors examine the social, environmental, cultural and psychological determinants of health and illness and demonstrate that comprehesive primary health care address the health inequalities within these determinants, they also provide evidence to support the broad range of skills that health practitioners need to promote health and prevent illness. In this new edition, the authors have uniquely utilised two fundamental tenets central to all health promotion practice and developed key features from both the World Health Organisation's Ottawa Charter for Health Promotion and the International Union for Health Promotion and Education's Core COmpetencies for Health Promotion.
Includes bibliographical references and index.
Keywords: Health promotion; Primary health care; Australian